Wireless impact measurement for martial arts - Cowie, J. I.; Flint, J. A.; Harland, A. R. (The Engineering of sport 7, Volume 1, 2008)
The Integration of electronics into performance sports equipment has increased in recent years and with it the facility to provide more accurate judging, improved coaching, participant health monitoring and to enhance the entertainment of spectators. The focus in this paper is to respond to recent interest in various martial arts in quantifying and categorising impacts which occur during competition. An impact measurement technique has been developed which incorporates a non-invasive sensor System into a body protector worn in Taekwondo. The demonstrator System is integrated into the garment and utilises Bluetooth technology to transmit sensor readings back to a Computer for analysis. The sensors considered for impact measurement include thin film piezoresistive force and pressure sensors, and also much newer technologies such as MEMS (Micro-Electro-Mechanical Systems) accelerometers. Impact analysis has been carried out in both the frequency and time domain in order to determine the suitability of the different methods and the bandwidth requirements. The key metrics of force, pressure, velocity and impact duration have been assessed. It has been shown by field experiments and by employing standardised test methods that impacts can be best characterised by making use of various types of sensor in combination. Bluetooth allows for 100 m range; however it was found that the limited bandwidth afforded makes real time data capture problematic unless the sampling rate, bit resolution or number of channels is kept relatively small. In conclusion, a highly compact measurement System has been realised which is capable of quantifying martial arts impacts. The Bluetooth Standard is able to support the data transfer requirements, however development of a 'smart' on-garment sensor System would be the next logical step to manage a multi-sensor measurement System. This way the gathered data can be compressed or coded to reduce the transmission bandwidth.